Physiological performance in male handball players - Torres-Ronda, L.; Gerona, T.; González-Badillo, J. J. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Few studies have evaluated specific physiological performance measures in male handball players (Ziv & Lidor, 2009). The aim of the present study was to analyze physiological characteristics of men`s handball players according to age group and specific positional roles. Methods: Eighty players from F.C. Barcelona handball teams volunteered to take part in this study (Senior-b:n=15;Under-18:n=16;Under-16a:n=17;Under- 16b:n=16;Under-14:n=16). Players were measured for anthropometry, horizontal explosive power (5J), agility (T-test), throw speed and repeated sprint (6 x 12.5 m) and CMJ sequences. Results: Results showed the experience of age in fitness performance in handball players. Differences were evident in mean and best result of 5JT, jumping, standing and sitting throw and T-test (P<0.001). For the repeated sprint and jump sequences mean, best and % decrease in CMJ was significantly different between age groups (P<0.05), but not for sprint sequences. No differences between play positions (goalkeepers, playmarkers, backs, pivots and wings) were found. Finally, weight and height showed significant correlation between all performance measures (P<0.05) irrespective of age group. Discussion: The results indicate that age and years of training handball players aged 14 and over 20 years is an important determinant of performance in specific actions in the game, but not the relative endurance and the degree of fatigue reached when performing repeated sprints of the same distance. The fact that a significant correlation remains between weight and height and performance variables analyzed, independently of age, indicates that the weight and height are key variables in handball performance, which means that these variables are determinants of performance even when players have completed their biological and technical development (Mohamed, et al., 2009). These results suggest that there should be some difference in the testing analyzed between the different play positions, given the characteristics of height and weight between players. The lack of differences between play positions within each age could be explained by the small number of players within each team in various positions (Chaouachi, et al., 2009).